Does Foreign Direct Investment Build The Capabilities Of The Host Country? Evidence From Malaysia - Ling, Renee Mei Yen (2003)
Given appropriate host country policies and a basic level of development, a preponderance of studies show that foreign direct investment provides numerous benefits as well as costs to the host country. As the empirical evidence remains inconclusive, this paper is an attempt to contribute further to this debate by focussing on six non-resource and resource based industries in the Malaysian manufacturing sector from 1980 to 2001. By adopting the coefficient of correlation as the central statistical technique, empirical results infer only strong evidence that FDI builds the capabilities of the host country in two non-resource based industries namely the Electronics and Electrical products and Textiles and Textiles products industries. Lack of technology acquisition capabilities, shortage of specialised and skilled labour and deficiencies in supporting industries represent the main reasons behind the weak correlation observed for the Machinery Manufacturing, Chemical and Chemical products, Wood and Wood products and Rubber products industries. The results reflect the narrow-based positive' effects of FDI in the Malaysian manufacturing sector and also explicate the Government's recent amendments to its investment incentives towards the promotion of the four latter industries.